The learning curve for laparoscopic colectomy in colorectal cancer at a new regional hospital - Kuei-Yen Tsai; Kee-Thai Kiu; Ming-Te Huang; Chih-Hsiung Wu; Tung-Cheng Chang (Asian Journal of Surgery, 2016)
Background: Laparoscopic colorectal surgery has been extensively used, although mostly performed in medical centers or university hospitals. We analyzed the learning curve of laparoscopic colectomy in a new regional hospital and determined the experience necessary to achieve proficiency. Methods: From July 2008 to December 2013, the retrospective clinical study enrolled 240 patients who underwent laparoscopic colectomy. They were sequentially divided into Group A (Patients 1–80), Group B (Patients 81–160), and Group C (Patients 161–240). Patient demographics and perioperative parameters were analyzed. Operation time, as a measure of learning time, was analyzed using the moving-average method. Results: All patients were comparable for age, gender, body mass index, tumor location, cancer stage, length of hospital stay, intraoperative complication, morbidity, and mortality. Group A experienced more blood loss (p < 0.01) and longer operation time (p < 0.001). All laparoscopic operation time stabilized after 85 cases. Subgroup analysis showed that operation time stabilized after 15 cases for right hemicolectomy, 15 cases for sigmoidectomy, and 22 cases for low anterior resection with total mesorectal excision. Conclusion: Laparoscopic colectomy for colorectal cancer in a new regional hospital is feasible and safe. It does not need additional time for learning. Laparoscopic sigmoidectomy can be considered as the initial surgery for a trainee.